2019
DOI: 10.3892/etm.2019.7429
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑638 expression change in osteosarcoma patients via PLD1 and VEGF expression

Abstract: The present study aimed to investigate the function and mechanism of microRNA-638 (miR-638) in osteosarcoma. MiR-638 expression change in patients with osteosarcoma was detected by reverse transcription-quantitative polymerase chain reaction. Expression of miR-638 was observed to be downregulated in patients with osteosarcoma compared with the control group. In vitro , overexpression of miR-638 induced apoptosis, and inhibited cell proliferation and invasion of osteosarcoma cells. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…VEGF activates pro-survival signaling pathways leading to tumor growth and ultimately malignancy [5][6][7][8][9][10]. Therefore, a number of studies have been performed to investigate VEGF expression from solid tumors; it is critical and necessary to understand the intricate balance between pro-survival and anti-survival tendencies of tumors and detect potential malignancy [4,9,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF activates pro-survival signaling pathways leading to tumor growth and ultimately malignancy [5][6][7][8][9][10]. Therefore, a number of studies have been performed to investigate VEGF expression from solid tumors; it is critical and necessary to understand the intricate balance between pro-survival and anti-survival tendencies of tumors and detect potential malignancy [4,9,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies of VEGF secretion from the spheroids using microfluidic systems are limited to qualitative or semi-quantitative analysis based on analysis of RNA [ 7 , 16 , 17 , 43 ] rather than direct measurement of the protein itself. Several studies using anti-cancer agents on spheroid systems have concluded that physical properties of spheroids are related to drug efficacy [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hu et al reported that the expression of miR-1285-3p in OS tissues and cell lines was downregulated and associated with patients' overall survival [21]. Xue et al focused on the role of miR-638 in OS progression and demonstrated that miR-638 could enhance OS cell apoptosis and inhibit cell proliferation and invasion [22]. miR-1826 has been studied in some human cancers, such as melanoma [14], colorectal carcinoma [13], renal cancer [15], and bladder cancer [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high doses of chemotherapeutic agents have side effects (9). Therefore, understanding the molecular mechanism underlying the occurrence and development of Os could aid in the discovery of novel targets for Os treatment (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%